A new cryptic species of the Chrysoperla carnea group (Neuroptera: Chrysopidae) from western Asia: parallel speciation without ecological adaptation. (April 2014) - HENRY, CHARLES S.; BROOKS, STEPHEN J.; JOHNSON, JAMES B.; MOCHIZUKI, ATSUSHI; DUELLI, PETER
Abstract Parallel (or convergent) evolution of vibrational mating songs between species confined to different continents has been found several times in the Chrysoperla carnea species‐group of cryptic (morphologically indistinguishable) green lacewings. Repeated parallel speciation resulting in taxa that differ in duetting songs but not in appearance or ecology suggests an atypical mode of speciation, one that need not involve ecological adaptation. Here we describe an additional example of convergent song phenotypes reflecting parallel nonadaptive speciation, between the common North American species Chrysoperla plorabunda (Fitch) and a newly discovered species that appears to be widespread in western Asia. To support the hypothesis of parallel evolution, we describe the song of the new species in detail, comparing it to that of C. plorabunda and demonstrate their acoustical similarity. Results of song playback trials are then presented, showing that the songs are also functionally (behaviourally) indistinguishable between individuals of both species and could not prevent hybridisation if the two species were sympatric. We demonstrate that the new species is very similar in morphology and ecology not only to C. plorabunda, but also to at least four other species in the carnea‐group that co‐occur with it in western Asia. To reject the alternative hypothesis that C. plorabunda and the new species are alike simply due to common ancestry, we show that they occupy relatively distant positions in a phylogenetic analysis of 4630 base pairs of protein‐coding mitochondrial DNA. We then formally describe the new species as Chrysoperla heidariisp.n., including with this description observations of its behaviour, ecology and life history. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:60C0FFC5‐92B9‐4C20‐9FDF‐561EB2764F16.